2020
DOI: 10.1175/jamc-d-19-0057.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Monin–Obukhov and Bulk Richardson Parameterizations for Surface–Atmosphere Exchange

Abstract: The Land–Atmosphere Feedback Experiment (LAFE) was a field campaign to investigate influences of different land surface types on the atmospheric boundary layer (ABL). The primary goals of LAFE were to better understand ABL development and structure and to improve turbulence parameterizations in numerical weather prediction models. Three 10-m micrometeorological towers were installed over different land surface types (i.e., early growth soybean, native grassland, and mature soybean) along a 1.7-km southwest–nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The setup is presented in Figure 1 and the operating parameters of all lidars are listed in Table 1. The land cover at the EB stations was a mixture of grassland and soybeans at TWR 1, native grassland at TWR 2, mature soybeans at TWR 3, and pasture at TWR 4 (Lee & Buban, 2020; Wulfmeyer at al., 2018).…”
Section: The Land Atmosphere Feedback Experiments (Lafe)mentioning
confidence: 99%
See 1 more Smart Citation
“…The setup is presented in Figure 1 and the operating parameters of all lidars are listed in Table 1. The land cover at the EB stations was a mixture of grassland and soybeans at TWR 1, native grassland at TWR 2, mature soybeans at TWR 3, and pasture at TWR 4 (Lee & Buban, 2020; Wulfmeyer at al., 2018).…”
Section: The Land Atmosphere Feedback Experiments (Lafe)mentioning
confidence: 99%
“…Gradient and further flux measurements are made with additional sensors located at approx. 10 m above the canopy (Lee & Buban, 2020; Lee et al., 2019). Further insight in SL profiles and gradients have been achieved with sensors at different levels at high towers such as at the German Weather Service Lindenberg Meteorological Observatory ‐ Richard Assmann Observatory (Neisser et al., 2002), the Boulder tower (Wolfe & Lataitis, 2018), the WLEF‐TV tower in Wisconsin (Berger et al., 2001), the tower in Cabauw (Röckmann et al., 2016), and the Amazon Tall Tower Observatory (Andreae et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The absence of explicit documentation of this effect in the literature might be related to the fact that wet soils with short vegetation and large solar irradiation are not so common [being the aforementioned work of Lee and Buban (2020) an exception]. The pioneering works of Businger or Dyer were made essentially over dry terrain.…”
Section: Daytime Cases With Moist Soilmentioning
confidence: 99%
“…Major uncertainties of the MOST method are associated with the influence of complex/heterogeneous terrain, uncertainties in prescribing vegetation roughness and corrections for atmospheric stability (Holwerda et al, 2012;Sun et al, 2020;van Dijk et al, 2015;Zhou et al, 2012). Lee and Buban (2020) found that the Richardson number stability correction functions based on bulk meteorological variables yielded better agreement with field observations than using MOST relationships. These challenges are further exacerbated by the ambiguity in estimating the difference between r aM and the r a for heat transfer (r aH ), whereby complexity is added due to the inequality of LST and the aerodynamic temperature (T 0 ) (Paul et al, 2014).…”
Section: Introductionmentioning
confidence: 99%